Sustainable education and open innovation for small industry sustainability post COVID-19 pandemic in Indonesia - Anne Charina; Ganjar Kurnia; Asep Mulyana; Kosuke Mizuno (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
COVID-19 severely impacted small industries in Indonesia and many collapsed. Sustainable education is essential to help small industries recover post-pandemic through an open innovation design program to improve small industries' economic, social, and environmental performance. This paper examined the impacts of the sustainable education program implemented and explored open innovations suitable for the sustainability of small industries in developing countries, such as Indonesia, after the pandemic. This research employed a Participatory Action Research (PAR) approach involving academics, government, the community, and four small industries in West Java, Indonesia. Our findings reveal that the sustainable education program through learning activities and direct practice provides valuable knowledge and experience for small industries in designing economic, social, and environmental innovations. Open innovations post-pandemic suitable for small industries in Indonesia include simple business digitalization for company economic growth, the recruitment of people losing their jobs due to the pandemic to achieve social benefits, and innovations in using environmentally friendly packaging and charcoal briquette fuel as an environmental awareness effort. This study recommends that the open innovation designed for small industries be right on target and done using a participatory method to achieve sustainability after the COVID-19 pandemic.
Keywords: 650; open innovation; participatory; post COVID-19 pandemic; small industry sustainability; sustainable education